1991
DOI: 10.1099/00221287-137-2-351
|View full text |Cite
|
Sign up to set email alerts
|

The bialaphos biosynthetic genes of Streptomyces viridochromogenes: cloning, heterospecific expression, and comparison with the genes of Streptomyces hygroscopicus

Abstract: The bialaphos resistance gene, bar, was used as a selectable marker to isolate the bialaphos production genes (bap) from the Sfreptomyces uiridochromogenes genome. The S. uiridochromogenes bar gene was cloned on overlapping restriction fragments using pIJ680 and pIJ702 in the bialaphos-sensitive host, S. Zittidans. Although the restriction endonuclease cleavage map of these fragments was not similar to the bap cluster of S. hygroscopicus, the presence and location of bar and four other bap genes as well as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…hygroscopicus cluster further substantiate previous mapping efforts that predicted the architecture of the two gene clusters were identical (13). The amino acid identity of S. viridochromogenes genes compared to published S. hygroscopicus homologs range from very highly conserved at 95.5% for the bcpA/phpI homolog pair from the core region of the PTT cluster to 63.9% for the phpR/brpA homologs located at the far downstream flank of the gene cluster.…”
Section: Figsupporting
confidence: 72%
See 1 more Smart Citation
“…hygroscopicus cluster further substantiate previous mapping efforts that predicted the architecture of the two gene clusters were identical (13). The amino acid identity of S. viridochromogenes genes compared to published S. hygroscopicus homologs range from very highly conserved at 95.5% for the bcpA/phpI homolog pair from the core region of the PTT cluster to 63.9% for the phpR/brpA homologs located at the far downstream flank of the gene cluster.…”
Section: Figsupporting
confidence: 72%
“…The S. viridochromogenes genes and enzymes responsible for the initiation of phosphinothricin biosynthesis and production of phosphonoacetaldehyde (steps I and II), involving genes ppm and ppd, have been described previously (17,32,42) and were readily identified in our sequence; however, relatively little is known about the next two steps, the conversion of phosphonoacetaldehyde to hydroxymethylphosphonate (step III) and the subsequent oxidation of hydroxymethylphosphonate to phosphonoformate (step IV). S. hygroscopicus mutants blocked at both steps in the pathway could be complemented in trans by an unsequenced region of DNA closely linked to the ppm and ppd genes from either S. hygroscopicus (21,31) or S. viridochromogenes (13). The arrangement of the complementing genes within the unsequenced region was refined by restriction to at least two separate ORFs upstream of ppm, with step III complementing DNA localizing directly upstream from the step IV complementing sequence (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses indicated that location of the group of genes comprised of phpC, phpD, and phpE in the PTT gene cluster suggested that they could have roles in the conversion of phosphonoacetaldehyde to phosphonoformate (Fig 1b, steps III and IV) 7,15 . The role of phpC was unknown and its homology to type III (iron-dependent) alcohol dehydrogenases did not suggest an obvious function for the gene in PTT biosynthesis.…”
mentioning
confidence: 99%
“…To test if PhpC acts as a phosphonoacetaldehyde reductase, we purified a histidine-tagged PhpC fusion after overexpression in Streptomyces lividans. His-PhpC catalyzed the in vitro reduction of phosphonoacetaldehyde to hydroxyethylphosphonate (HEP, 14) with either NADH (15) or NADPH (16) as a cofactor using 31 P NMR spectroscopy (Fig. 2) and LC/MS (Table 1, Supplementary Fig.…”
mentioning
confidence: 99%
“…The pathways leading to the commercially important antibiotic fosfomycin (16) and herbicide bialaphos (17) have been elucidated (14,15,30), as has the pathway leading to AEP (18) (Fig. 1).…”
mentioning
confidence: 99%